KAJIAN STRUKTUR 10 LANTAI GEDUNG DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN KUTAI KARTANEGARA - PRAMANA PUTRA, ANGGI (KURVA S JURNAL MAHASISWA, 2016)
Nowadays, almost every city in Indonesia are competing in upgrading the number of development. The development is being done towards the facilities and infrastructure in each city in order to support citizen’s daily needs, such as building construction, bridge construction, road construction, etc. Increasing of development number is also happening in Tenggarong City. This increasing of development number will affect the number of jobs vacancies, so that many constructions expert will be needed. Based on this problem, a construction of an office building, named Manpower and Transmigration of Kutai Kertanegara Tenggarong Building is planned. This building construction is planned because it has an important role for the citizen to provide jobs vacancies for them in their own competence. This research will discuss how to calculate building structure using matrix method and SAP2000 method. This research aims to know any loads that include in the structure.